Розвідки у південній частині Чернівецької обл. - Шманько, О.В. (Археологічні дослідження в Україні, 2010)
The paper concerns the inspection of monuments in the south of Chernivtsi Oblast (Hlyboka Region). Most of the materials belong to Trypillya culture, one hill-fort relates to Holihrady culture. Unsatisfactory condition of preservation of the monuments and the necessity of measures for their salvation are emphasized.